Feasibility of a wearable soft-robotic glove to support impaired hand function in stroke patients - Bob Radder; Gerdienke Prange-Lasonder; Anke I. R. Kottink; Alejandro Melendez-Calderon; Jaap H. Buurke; Johan S. Rietman (Medical Journals Sweden, 2018)
Objective: To investigate the feasibility of a wear-able, soft-robotic glove system developed to combine assistive support in daily life with performing therapeutic exercises on a computer at home (the HandinMind system). Design: Feasibility study. Patients: Five chronic stroke patients with limitations in activities of daily living due to impaired hand function. Methods: Participants performed a usability test and several functional tasks with the HandinMind system across 2 sessions. Feasibility was measured using the System Usability Scale (SUS), Intrinsic Motivation Inventory (IMI) and performance times of the functional tasks. Results: User acceptance measured by the SUS and IMI was scored high. The median SUS scores of sessions 1 and 2 were 80.0 (interquartile range (IQR) 70.0-88.8) and 77.5 (IQR 75.0-87.5), respectively, and the median IMI score was 6.3 points out of 7 points (IQR 6.2-6.3). Functional task performance was initially slower with the HandinMind glove compared with performance without the glove, but improved up to the level of performance without the glove across no more than 3 repetitions. Conclusion: Chronic stroke patients with impaired hand function were positive about the feasibility of the first prototype of the HandinMind system. How-ever, performance and ease of use of the system should be improved further in future development phases.